HLA Class Ib Molecules and Immune Cells in Pregnancy and Preeclampsia - Djurisic, Snezana; Hviid, Thomas Vauvert F. (Frontiers in Immunology, 2014)
Despite decades of research, the highly prevalent pregnancy complication preeclampsia, ‘the disease of theories’, has remained an enigma. Indeed, the etiology of preeclampsia is largely unknown. A compiling amount of studies indicate that the pathological basis involves a complex array of genetic predisposition and immunological maladaptation, and that a contribution from the mother, the father and the fetus is likely to be important. The Human Leukocyte Antigen (HLA) –G is an increasing focus of research in relation to preeclampsia. The HLA-G molecule is primarily expressed by the extravillous trophoblast cells lining the placenta together with the two other HLA class Ib molecules, HLA-E and HLA-F. Soluble isoforms of HLA-G have been detected in the early endometrium, the matured cumulus-oocyte complex, maternal blood of pregnant women, in umbilical cord blood, and lately, in seminal plasma. HLA-G is believed to be involved in modulating immune responses in the context of vascular remodeling during pregnancy as well as in dampening potential harmful immune attacks raised against the semi-allogeneic fetus. In addition, HLA-G genetic variants are associated with both membrane-bound and soluble forms of HLA-G, and, in some studies, with preeclampsia. In this review, a genetic contribution from the mother, the father and the fetus, together with the presence and function of various immune cells of relevance in pregnancy, are reviewed in relation to HLA-G and preeclampsia.